Innovative Optogenetic Strategies for Vision Restoration - Baker, Cameron K.; Flannery, John G. (Frontiers in Cellular Neuroscience, 2018)
The advent of optogenetics has ushered in a new era in neuroscience where spatiotemporal control of neurons is possible through light application. A major driver behind optogenetic tool development is vision restoration. In order to recapitulate the broad spectral and light sensitivities along with high temporal sensitivity found in human vision, researchers have identified and developed new optogenetic tools. There are two major kinds of optogenetic effectors employed in vision restoration: ion channels and G-protein coupled receptors (GPCRs). Ion channel based optogenetic therapies require high intensity light that can be unsafe at lower wavelengths, so work has been done to expand and red-shift the excitation spectra of these channels. Light activatable GPCRs are much more sensitive to light than their ion channel counterparts but are slower kinetically in terms of both activation and inactivation. This review examines the latest optogenetic ion channel and GPCR candidates for vision restoration based on light and temporal sensitivity.